Markers and Predictors of Proliferative Vitreoretinopathy in Open Eye Injury in an Experiment - A. A. Kol’bin; A. N. Kulikov; R. L. Troyanovsky; V. S. Chirskiy (Oftalʹmologiâ, 2024)
The objective of the study: to analyze characteristics of a standardized model of type B gunshot open global injury (open injury without intraocular foreign body).Methods: The experiment was carried out on 36 rabbits (71 eyes). Simulation of type B gunshot open global injury (GOEI) was accomplished using pump equipment. The complex of modern standard and hightechnology diagnostic methods to study characteristics of type B GOEI in the control period was performed. Biomicroscopy, ophthalmoscopy, optical coherence tomography, electroretinography, ultrasound examination, MRI, enzyme multiplied immunoassay to determine vitreous fibronectin, and pathomorphological study of the eye globe were carried out. Nonparametric statistical methods of data analysis were used.Results: The above diagnostic methods being used, the GOEI experimental model characteristics were determined, including proliferative vitreoretinopathy (PVR) i.e.incidence rate and dynamics.Conclusion. High reproducibility (77–100 %) of microlevel signs of type B GOEI experimental model was demonstrated, that evidenced standardization of the developed model. The viability of the use of hyphema and hemophthalmia as the PVR and GOEI predictors was justified on the basis of correlation analysis in experiment. The analysis of proliferative signs being made when using different study methods (pathomorphological, indirect ophthalmoscopy, optical coherence tomography, ultrasound examination and MRI) proved their application as PVR markers possible. The interchangeability of the study methods used for PVR diagnosis was also justified.